Fitness Discourse through Individual Posts on Instagram - Simanjuntak, Magda Sabrina Theofany (Jurnal Media dan Komunikasi Indonesia, 2024)
Background: The discourse on fitness is one of the prevalent discussions in contemporary society. The fitness discourse, as understood today, is rooted in scientific research and exerts influence over other discourses related to fitness. The most widely embraced notion of fitness by the general public revolves around health. Purpose: Researchers argue that social media has become a means of panopticism, where attributes such as physical activities and sportswear serve as representations of normalized body fitness. This study employs Foucault's arguments in observing the daily posts of social media users regarding body fitness discourses as a form of panopticism. Methods: The research embraces a post-positivist paradigm and employs a mixed methods approach, incorporating both quantitative and qualitative methods. The quantitative segment employs surveys, while the qualitative aspect utilizes in-depth interviews with three informants. Conclusion: The findings of this study illustrate how panopticism manifests in social media posts, encouraging individuals who utilize these platforms to partake in physical activities. Furthermore, the study uncovers how social media posts not only depict the existing reality but also facilitate a simulated reality. Implications: This research underscores how the discourse surrounding body fitness, disseminated through media practices, is perpetuated to bolster dominant groups within the cultural industry.